Składka kwantylowa w modelu ryzyka kolektywnego a dane szkodowe z obcięciem dolnym - Burnecki, Krzysztof; Nowicka-Zagrajek, Joanna (Quantile Premium in the Collective Risk Model with Left-Truncated Loss Distributions, 2006)
In the paper we discuss the quantile premium in the collective risk model framework. The model is fitted to incomplete insurance data. We study the influence of ignoring the threshold on the premium and the quality of various approximations presented in the literature.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 306-317